Utilization of polyepoxysuccinic acid as the green selective depressant for the clean flotation of phosphate ores. (1st February 2021) - Dong, Liuyang; Wei, Qian; Jiao, Fen; Qin, Wenqing
Abstract: In flotation, the application of some flotation reagents may cause serious water pollution and damage the ecological environment and human health. Large consumption of flotation reagents also restricts the sustainable production of mines. Therefore, the development and application of environmentally friendly and economical flotation reagents are essential for the sustainable production of phosphate ores and phosphate fertilizer. In this work, a non-nitrogen and phosphorus-free green, economical and environmentally friendly reagent, polyepoxysuccinic acid was used to evaluate its selective inhibition on calcite during apatite flotation. Micro-flotation experiments were used to investigate the floatability of the two minerals. Bench-scale flotation experiments were used to verify the efficiency of industrial application of polyepoxysuccinic acid in the flotation phosphate ores. Depression mechanism of polyepoxysuccinic acid was revealed through zeta potential measurements, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and atomic force microscope. The flotation separation of apatite and calcite can be achieved with polyepoxysuccinic acid using sodium oleate as collector. Bench-scale flotation experiments show that a good flotation index with a P2 O5 grade of 32.74% and a recovery of 84.82% can be obtained at a depressant dosage of 80 g/t. Mechanism experiment proved polyepoxysuccinic acid had a stronger adsorption on calcite than apatite. The adsorption of polyepoxysuccinic acid on calcite was mainly chemical adsorption through the chelation of its carboxyl group and calcium atoms. Therefore, this work provides a clean and economic reagent for the sustainable production of phosphate ores and phosphate fertilizer, which is of great significance for the sustainable development of clean mines. Graphical abstract: Image 1 Highlights: PESA is a non-phosphorus, non-nitrogen, clean depressant. A novel depressant PESA was introduced in phosphate ore flotation. PESA could achieve flotation separation of apatite from calcite. PESA could selectively and chemically adsorb on calcite surface. PESA is a promising depressant for sustainable production of phosphate ore.